2010
DOI: 10.1089/ten.tea.2010.0079
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic and Osteogenic Potential of Bone Repair Cells for Craniofacial Regeneration

Abstract: There has been increased interest in the therapeutic potential of bone marrow derived cells for tissue engineering applications. Bone repair cells (BRCs) represent a unique cell population generated via an ex vivo, closed-system, automated cell expansion process, to drive the propagation of highly osteogenic and angiogenic cells for bone engineering applications. The aims of this study were (1) to evaluate the in vitro osteogenic and angiogenic potential of BRCs, and (2) to evaluate the bone and vascular regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 41 publications
2
63
0
1
Order By: Relevance
“…For instance, MSCs, which may be isolated from bone marrow for osteoprogenitor cells, also have been shown to have the potential to differentiate toward an endothelial lineage. 288 Another attractive autologous source that may be used to isolate both osteo- and endothelial- progenitors is the stromal vascular fraction (SVF) of adipose tissue, which is abundantly available, easy to harvest, and associated with minimal donor site morbidity. In addition, in comparison to bone marrow, it has a much higher frequency of clono-genic mesenchymal progenitors compared.…”
Section: Recent Advances In Btementioning
confidence: 99%
“…For instance, MSCs, which may be isolated from bone marrow for osteoprogenitor cells, also have been shown to have the potential to differentiate toward an endothelial lineage. 288 Another attractive autologous source that may be used to isolate both osteo- and endothelial- progenitors is the stromal vascular fraction (SVF) of adipose tissue, which is abundantly available, easy to harvest, and associated with minimal donor site morbidity. In addition, in comparison to bone marrow, it has a much higher frequency of clono-genic mesenchymal progenitors compared.…”
Section: Recent Advances In Btementioning
confidence: 99%
“…These results demonstrate the strategic ability of BMSCs to help remediate a pathologic, nonhealing wound. BMSCs are currently being utilized in clinical trials for small bony defects in the craniofacial region, where they have shown to produce well-mineralized and well-vascularized jawbone regenerates [29]. Therefore, given institutional approval, there are no immediate regulatory impediments and ample precedent for the translation of this research into the operating suite.…”
Section: Deshpande Et Almentioning
confidence: 99%
“…Therefore, induction of vascularization is a crucial part of any successful bone regeneration strategy. In vitro and in vivo studies have shown the angiogenic potential of a number of bone substitute materials and their neovascularization capability [8,9]. Several growth factors play an important role in the process of angiogenesis, with the vascular endothelial growth factor (VEGF) family being one of these, which is also secreted from different cell types, like fibroblasts, bone marrow stromal cells, osteoblasts and osteoclasts [5,10].…”
Section: Introductionmentioning
confidence: 99%